2017
DOI: 10.1371/journal.pgen.1006846
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of huntingtin in the adult mouse leads to progressive behavioral deficits, bilateral thalamic calcification, and altered brain iron homeostasis

Abstract: Huntington’s Disease (HD) is an autosomal dominant progressive neurodegenerative disorder characterized by cognitive, behavioral and motor dysfunctions. HD is caused by a CAG repeat expansion in exon 1 of the HD gene that is translated into an expanded polyglutamine tract in the encoded protein, huntingtin (HTT). While the most significant neuropathology of HD occurs in the striatum, other brain regions are also affected and play an important role in HD pathology. To date there is no cure for HD, and recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 75 publications
3
73
0
2
Order By: Relevance
“…Whether overall reductions in cortical and hippocampal neuron abundance occurred, or only in newborn hippocampal neurons, was not addressed. In a more extensive study (Dietrich et al, 2017), adult Hdh flox/ − mice carrying the tamoxifen-inducible CAAGG-CreER™ allele were injected with tamoxifen to induce global cre-mediated recombination and huntingtin elimination at 3, 6 or 9 months of age. A progressive rotarod impairment was evident by one month after tamoxifen treatment, and severe gait abnormalities, hind limb clasping on tail suspension, and resting tremors were seen by 16 months of age in all mice with deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Whether overall reductions in cortical and hippocampal neuron abundance occurred, or only in newborn hippocampal neurons, was not addressed. In a more extensive study (Dietrich et al, 2017), adult Hdh flox/ − mice carrying the tamoxifen-inducible CAAGG-CreER™ allele were injected with tamoxifen to induce global cre-mediated recombination and huntingtin elimination at 3, 6 or 9 months of age. A progressive rotarod impairment was evident by one month after tamoxifen treatment, and severe gait abnormalities, hind limb clasping on tail suspension, and resting tremors were seen by 16 months of age in all mice with deletion.…”
Section: Discussionmentioning
confidence: 99%
“…One such therapeutic currently in clinical trials (IONIS-HTTRx, ClinicalTrials.org: NCT03342053) employs an intrathecal antisense oligonucleotide to non-selectively target the human HTT gene and reduce HTT expression in HD mutation carriers (Rodrigues and Wild, 2018). Although several studies in rodent and non-human primate models have shown that Htt knockdown in adult animals is not harmful (Wang et al, 2016a;McBride et al, 2011;Boudreau et al, 2009), one study found that Htt deletion in the adult mouse leads to brain atrophy, extensive reactive gliosis, and progressive motor symptoms (Dietrich et al, 2017). Our findings show that wild-type HTT plays an important role in both IP-SPNs and DP-SPNs, and preserving this function is critical for maintaining striatal health and function.…”
Section: Loss Of Htt In Spns Partially Recapitulates Several Hdlike Pmentioning
confidence: 99%
“…Carroll despairingly cites two almost identical studies 6,7 in mice that gave radically different results. "Right now, we don't know enough, " he says.…”
Section: The End Of the Beginningmentioning
confidence: 99%